Maritime-Based Early Childhood Curriculum Development Model - Nuryati, Nuryati; Mwila, Prospery M. (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah UI BBC, 2025)
This research is motivated by exploring the utilization of maritime potential in PAUD institutions in the coastal areas of Banten so that there are no future generations who have an interest in working in coastal areas in order to develop maritime potential. Study This aim develops design Early Childhood curriculum in the field relevant maritime​ with need public maritime on the Coast north of Old Banten. The method used in study This is a Dynamic model. Research and development with refers to the development model curriculum Dynamic Skilbeck. Research steps development This covering Analyze situation, Formulate Objectives, Program preparation, Interpretation and implementation, Monitoring, feedback, assessment and reconstruction. Data collection techniques include observation and interviews. Data analysis used is descriptive qualitative. Based on results research, design curriculum field maritime load four indicator namely ; (1) introducing identity​ nation Indonesia as nation maritime ; (2) building knowledge, awareness and understanding child to potential sea ; (3) develop learning programs based on projects ; and (4) building attitude proud and love homeland. While experience relevant learning​ with need public maritime that is learning based on project, child given experience direct in fish processing, and grass sea become material food in Indonesia, especially in the Banten region. This study provides significant contributions to the development of maritime-based curriculum for early childhood education by formulating five main indicators in the design of maritime curriculum.